Sog. kommodische und inkommodische Syntagmen im Deutschen und Polnischen - Bzdęga, Andrzej Z. (Wydawnictwo Naukowe UAM, 1984)
The subject of the article are verbal predicates of a type "odnieść zwycięstwo" (to gain a victory) and "ponieść klęskę" (to meet with a repulse) in German and Polish. The semantic relation occurring in the similar syntagms from the point of view of profit or usability includes the noun phrases, appropriately marked and characterized and secondarily the verb of which it is an argument. This relation from the point of view of syntax also includes the so called casus commodi and incommodi of the experiencer. In addition this relation takes places with verbs of a modal kind e.g. "życzyć", "wünschen" (to wish) and "hoffen", "mieć nadzieję" (to hope).